What is the role of non-surgical clinicians in the assessment and management of degenerative cervical myelopathy? – Insights from the RECODE-DCM peri-operative rehabilitation incubator - Rohil V. Chauhan; Andreas K. Demetriades; Timothy F. Boerger; Justin M. Lantz; Caroline Treanor; Sukhvinder Kalsi-Ryan; Vishal Kumar; Lianne Wood; Joshua Plener; Nicky Wilson; Maryse Fortin; Carlo Ammendolia; et al. (Brain and Spine)
Introduction: Evidence on degenerative cervical myelopathy (DCM) has frequently focussed on surgical management, overlooking the role of non-surgical clinicians. Their contributions in the patient journey remain largely underexplored in the literature. Research question: What is the role of non-surgical clinicians in the assessment and management of people with DCM? Material and methods: This narrative review synthesizes knowledge from a comprehensive MEDLINE search and the collective expertise of the RECODE-DCM Peri-Operative Rehabilitation Incubator, an expert working group hosted by Myelopathy.org. Key domains of non-surgical clinician involvement include: 1) early recognition and referral, 2) patient education, 3) pain management, 4) preoperative management, and 5) postoperative rehabilitation. Results: Timely DCM diagnosis depends on first-contact clinicians recognizing hallmark symptoms. In the absence of standardized screening criteria, tools like the modified Japanese Orthopaedic Association score can support early identification. Non-surgical clinicians educate patients with mild or non-myelopathic spinal cord compression to recognize signs of DCM progression, ensuring timely surgical consultation. These clinicians also play a multidisciplinary role in the biopsychosocial management of pain, incorporating pharmacological and non-pharmacological strategies to address nociceptive and neuropathic pain. While predictors of postoperative outcomes, such as disease severity, gait dysfunction and smoking, are known, evidence on preoperative optimization and prehabilitation remains limited. Emerging research highlights the benefits of early postoperative rehabilitation, including cervical range of motion and stabilization exercises, in improving 12-month postoperative outcomes. Discussion and conclusion: Non-surgical clinicians play an integral role in DCM management across the care continuum. A multidisciplinary, patient-centred approach is essential. Postoperative rehabilitation holds promise, but prospective trials are necessary to establish standardization and optimal strategies for clinical delivery.